2003
DOI: 10.1074/jbc.m306431200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Chemoenzymatic Synthesis of Monodisperse Hyaluronan Oligosaccharides with Immobilized Enzyme Reactors

Abstract: We describe the chemoenzymatic synthesis of a variety of monodisperse hyaluronan (␤4-glucuronic acid-␤3-N-acetylglucosamine (HA)) oligosaccharides. Potential medical applications for HA oligosaccharides (ϳ10 -20 sugars in length) include killing cancerous tumors and enhancing wound vascularization. Previously, the lack of defined oligosaccharides has limited the exploration of these sugars as components of new therapeutics. The Pasteurella multocida HA synthase, pmHAS, a polymerizing enzyme that normally elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 20 publications
(27 reference statements)
1
76
0
Order By: Relevance
“…A useful property of pmHAS is that it can extend exogenously provided HA acceptor oligosaccharides in vitro (16). This polymerization reaction occurs in a nonprocessive fashion where the enzyme binds, elongates, and releases the growing HA chain in a rapid repetitive fashion (13,17). In this report, we utilize the acceptor elongation activity for the chemoenzymatic synthesis of a variety of HA polymers with narrow size distributions.…”
Section: Hyaluronan (Ha)mentioning
confidence: 99%
“…A useful property of pmHAS is that it can extend exogenously provided HA acceptor oligosaccharides in vitro (16). This polymerization reaction occurs in a nonprocessive fashion where the enzyme binds, elongates, and releases the growing HA chain in a rapid repetitive fashion (13,17). In this report, we utilize the acceptor elongation activity for the chemoenzymatic synthesis of a variety of HA polymers with narrow size distributions.…”
Section: Hyaluronan (Ha)mentioning
confidence: 99%
“…Overall, PmHAS appears to be a polypeptide with two active sites involved with coordinated but intrinsically nonprocessive activities. In several indirect tests, including in vitro syntheses of oligosaccharides [21] and polysaccharides [29], PmHAS appears to operate in a nonprocessive fashion. In vivo, PmHAS is probably docked with the membrane transport machinery which may not allow the HA chain to diffuse far away from the microenvironment of the two active sites.…”
Section: Resultsmentioning
confidence: 99%
“…For MALDI-ToF MS and SEC-MALLS analyses, a preparation of PmHAS 1-703 was purified by chromatography on Toyopearl Red AF resin (Tosoh Corp., Tokyo, Japan) using salt elution (50 mM HEPES, pH 7.2, 1 M ethylene glycol with 0 to 1.5 M NaCl gradient in 1 hour) as described previously [21]. The fractions containing the target protein (~95% pure by SDS-PAGE/Coomassie-staining) were pooled and concentrated by ultrafiltration.…”
Section: Production Of Recombinant Truncated Pmhas Proteinmentioning
confidence: 99%
“…rhHAS2-(122-414) could not synthesize longer (high molecular weight) HA chains even by using longer incubations (over 24 h) or reactions with higher UDP-sugar concentrations (data not shown). Incubation of the tetrasaccharide acceptor with a single donor, UDP-GlcNAc, did not yield HA5, suggesting that the recombinant truncated HAS2 polypeptides cannot be utilized for the stepwise synthesis of HA performed by using the engineered PmHAS method reported by DeAngelis et al (25). For the purpose of the regulation of the molecular size of the HA, some improvement or optimization of the reaction conditions will be required.…”
Section: Production Of Rhhas2 Fusion Proteins In E Coli-it Has Beenmentioning
confidence: 99%
“…It has also been reported that PmHAS added new sugar residues to the saturated tetramer prepared by means of ovine testis hyaluronidase at the non-reducing end (17). Moreover the recent work of DeAngelis et al (25) clearly demonstrated that the engineered PmHAS could be converted into two single action glycosyltransferases, and reactor enzymes immobilized onto solid supports were utilized in an alternating fashion to make pure HA molecules of a single length in a controlled and stepwise manner. In vertebrates HASs, it is known that HAS of Xenopus DG42 expressed in yeast exhibited a significant activity as HA synthase (26).…”
mentioning
confidence: 99%